2000
DOI: 10.1002/(sici)1096-8644(2000)112:2<159::aid-ajpa3>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Food consumption, activity, and overweight among elementary school children in an Appalachian Kentucky community

Abstract: In the U.S., child overweight is on the rise and is implicated in later adult chronic illness. Given that overweight is hardly tractable, prevention as compared to treatment is seen as a better alternative for lowering the risk of long-term health consequences. To increase the success of prevention efforts, many argue that programs must be "culturally sensitive and targeted toward specific populations at greater risk. However, there exists a limited understanding of how overweight is distributed across the lan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 32 publications
3
39
1
Order By: Relevance
“…As seen in other studies, it is a misconception that obese children and adolescents consume more "junk food" than the non-obese [26,28,29]. Our study confirms this for high calorie foods, not found in Canada's Food Guide, as a whole, but did show that potato chips are consumed significantly more often by obese youth.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As seen in other studies, it is a misconception that obese children and adolescents consume more "junk food" than the non-obese [26,28,29]. Our study confirms this for high calorie foods, not found in Canada's Food Guide, as a whole, but did show that potato chips are consumed significantly more often by obese youth.…”
Section: Discussionsupporting
confidence: 91%
“…Generally, obese and non-obese youth eat similar number of servings from the food groups which are below current recommendations [26,28,29]. In the current study the obese consumed more grain products and meat than did the nonobese, perhaps because of the amount of FAFH consumed.…”
Section: Discussioncontrasting
confidence: 56%
“…To maintain energy balance, lower levels of physical activity should be accompanied by lower caloric intake (7). Dietary behaviors that have been associated with lower BMI include the consumption of fruit (8, 9) and vegetables (9). In contrast, high dietary fat intake and increased consumption of sweetened beverages are associated with increased caloric intake and body weight (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the preference for dense-energy food and sugary drink, it showed that rural and urban school children have a similarity in higher fat intake (Crooks, 2000). The popularity of fast foods and soft drinks, less exercise, increased television viewing, and computer use are the common trends that influenced nutrition and lifestyle of the children today (Unnithan & Syamakumari, 2008).…”
Section: Body Mass Index (Bmi) and Socio-cultural Environmentmentioning
confidence: 99%